Sustainable Design of a Near-Zero-Emissions Building Assisted by a Smart Hybrid Renewable Microgrid - Mostafa Esmaeili Shayan; Gholamhassan Najafi; Barat Ghobadian; Shiva Gorjian; Mohamed Mazlan (Center of Biomass & Renewable Energy, Diponegoro University, 2022)
Renewable energy regulations place a premium on both the use of renewable energy sources and energy efficiency improvements. One of the growing milestones in building construction is the invention of green cottages. Building Integrated Photovoltaic (BIPV) technologies have been proved to aid buildings that partially meet their energy demand as sustainable solar energy generating technologies throughout the previous decade. Curved facades provide a challenge for typical photovoltaics. This study designed, produced, and assessed elastic solar panels supported by flexible photovoltaic systems (FPVS) on a 1 m2 layer. The LabVIEW program recognizes and transmits online data on warm and dry climates. The fill factor was 88% and 84%, respectively, when installed on the silo and biogas surfaces. The annual energy output was 810 kWh on a flat surface, 960 kWh on a cylindrical surface, and 1000 kWh on a hemisphere surface. Economic analysis indicates that the NPV at Flat surface is 697.52, with an IRR of 34.81% and an 8.5-year capital return period. Cylindrical surfaces and hemispheres both get a 955.18 increase. For cylindrical and hemispheric buildings, the investment yield was 39.29% and 40.47%, respectively. A 20% increase in fixed investment boosted the IRR by 21.3% in the flat system. While the cylindrical system had a 25.59% raise, the hemisphere saw a 24.58% gain